The Relationship between the Personality Traits and Self-Compassion with Psychological Well-Being in Iranian College Students: A Cross-Cultural Study - Jelodari, Arash; Kord Azizpour Mohamamdi, Rezvan (International Journal of Education and Cognitive Sciences, 2022)
It has been well established that personality traits and self-compassion are associated with psychological well-being, thus, the current research aimed to investigate the underlying mechanisms in a collectivist culture. One hundred and fifty college students were chosen and filled out Ryff's Psychological Well-Being Scale, the NEO Personality Inventory, and Neff's Self-Compassion Scale. The results of correlation analysis showed that there were significant relationships between the personality traits (neuroticism, extraversion, agreeableness, and conscientiousness) and self-compassion (self-kindness, isolation, mindfulness, and the total score of self-compassion) with psychological well-being. The regression analysis showed that neuroticism, extraversion, and conscientiousness significantly predicted psychological well-being. The cultural implications and future orientations have been discussed.